PENGARUH LOAN TO ASSET RATIO, DEBT EQUITY RATIO, NET PROFIT MARGIN DAN PRICE TO BOOK VALUE PADA RETURN BANK - Lupita Siwi, Ni Putu Anning widar Ayu; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
Return shares are income obtained by the shareholders as a result of investments in companies. This research aims to understand the influence of Loan to Asset Ratio (LAR), Debt Equity Ratio (DER), Net Profit Margin (NPM), and Price to Book Value (PBV) on return the stocks of banking concerns listed on the indonesia stock exchange of an observation the 2010-2014. The total sample in this research as many as 15 banking company which is listed on the indonesia stock exchange with sample purposeve as a method of the sample collection. The data used represents data skunder and techniques of the analysis used is that multiple linear regression. The results show that the testing LAR, NPM and PBV have had a positive impact on return share, while DER not have had a positive impact on return shsre.
Keywords: Loan to Asset Ratio, Debt Equity Ratio, Net Profit Margin, Price to Book Value, Return